Pediatric anti-myelin oligodendrocyte glycoprotein syndrome: case series of a newly recognized central nervous system inflammatory disease. (3rd June 2015) - Venkateswaran, S; Thulasirajah, S; Pohl, D; Rostasy, K
Abstract : Pediatric acquired demyelinating syndromes have overlapping clinical and imaging features, but management and prognosis vary. We describe four children between the ages of 3 and 10 presenting with inflammatory brain disease - one with polyfocal neurological symptoms, one with severe bilateral optic neuritis and two with transverse myelitis, all without encephalopathy. All brain MRIs had extensive involvement of both deep grey and subcortical white matter. Three patients had longitudinally extensive spinal cord lesions. Clinical and radiological findings did not meet criteria for multiple sclerosis, acute disseminated encephalomyelitis, or neuromyelitis optica (NMO). NMO IgG testing was negative. All patients had resolution of clinical and imaging findings after treatment with steroids and IVIg. We found, elevated levels of anti-myelin oligodendrocyte glycoprotein antibodies in all four patients. Three of the children receive monthly IVIg infusions. Two of the patients relapsed once within 18 months of their initial attack and have since remained relapse free for 32 months and 43 months, respectively. The third patient (transverse myelitis) has not had any relapses since her initial attack 15 months ago. It appears that children with this syndrome may have more favourable outcomes when compared to other CNS relapsing inflammatory conditions.